Orbital-period Changes of Low-mass X-Ray Binaries Driven by Magnetic Braking - Yun-Ning Fan; Yong Shao; Wen-Cong Chen (The Astrophysical Journal)
Magnetic braking (MB) plays an important role in driving the evolution of low-mass X-ray binaries (LMXBs). The modified MB prescription, the convection and rotation boosted (CARB) model, is very successful in reproducing the detected mass-transfer rates of persistent neutron star (NS) LMXBs. In this work, we investigate whether the CARB MB prescription could account for the formation and evolution of some NS and black hole (BH) LMXBs with an observed orbital-period derivative. Using the MESA code, we perform a detailed binary evolution model for six NS and three BH LMXBs. Our simulations find that the CARB MB prescription can successfully reproduce the observed donor-star masses, orbital periods, and period derivatives of four NS LMXBs and one BH LMXB. Our calculated effective temperatures are in good agreement with the detected spectral types of two NS LMXBs and one BH LMXB. However, the standard MB model makes it difficult to produce the observed period derivatives of those LMXBs experiencing a rapid orbital shrinkage or expansion.